SCS Method Application in Construction of the Runoff Hydrograph (Proceedings of Faculty of Civil Engineering, 2022)
Application of the SCS method in the Republic of Croatia is primarily based on manuals from foreign sources and already prepared software packages. This paper will present a brief history of the SCS method development and its characteristics, as well as the process of calculation of the flow and construction of the runoff hydrographs. The application of the SCS method for the runoff precipitation assessment in the maximum runoff calculation by usage of Ven Te Chow method and Goudrich expression for modifying and defining all hydrograph points are described in detail. The example of a calculation on the Slani potok catchment is presented.
Keywords: SCS method; runoff hydrograph; Slani potok